2012
DOI: 10.1128/jvi.00177-12
|View full text |Cite
|
Sign up to set email alerts
|

Porcine Reproductive and Respiratory Syndrome Virus Induces Interleukin-15 through the NF-κB Signaling Pathway

Abstract: Porcine reproductive and respiratory syndrome virus (PRRSV) mainly infects macrophages/dendritic cells and modulates cytokine expression in these cells. Interleukin-15 (IL-15) is a pleiotropic cytokine involved in wide range of biological activities. It has been shown to be essential for the generation, activation, and proliferation of NK and NKT cells and for the survival and activation of CD8 ؉ effector and memory T cells. In this study, we discovered that PRRSV infection upregulated IL-15 production at both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 64 publications
2
35
0
Order By: Relevance
“…Inhibition of NF-B activation by pyrrolidine dithiocarbamate leads to a significant decrease in the levels of heparanase (20), indicating that NF-B might be an important regulator of heparanase. A number of reports have also demonstrated that PRRSV infection can activate the NF-B signaling pathway by IB␣ degradation and nuclear translocation of p65, a key subunit of NF-B (21,22). We therefore investigated the possible connection between NF-B and heparanase after PRRSV infection.…”
Section: Resultsmentioning
confidence: 99%
“…Inhibition of NF-B activation by pyrrolidine dithiocarbamate leads to a significant decrease in the levels of heparanase (20), indicating that NF-B might be an important regulator of heparanase. A number of reports have also demonstrated that PRRSV infection can activate the NF-B signaling pathway by IB␣ degradation and nuclear translocation of p65, a key subunit of NF-B (21,22). We therefore investigated the possible connection between NF-B and heparanase after PRRSV infection.…”
Section: Resultsmentioning
confidence: 99%
“…1G), suggesting that NF-kB binding site 1 is critical for the upregulation of pri-miR-30c-2 by PRRSV. NF-kB can be activated by PRRSV infection (40). To investigate whether the activation of NF-kB is coincident with miR-30c induction, we performed a time-course analysis to determine the activation of NF-kB in PRRSV-infected cells.…”
Section: Mir-30c Is Upregulated By Prrsv Through Activating Nf-kbmentioning
confidence: 99%
“…Our previous work shows that PRRSV induces IL-15 production through NF-κB signaling pathway (Fu et al, 2012). However, the mechanism about how PRRSV activates NF-κB to up-regulate IL-15 is not complete.…”
Section: Introductionmentioning
confidence: 99%
“…PRRSV infection triggers the altered expression of many cytokines including the up-regulation of IL-15 Fu et al, 2012;Hou et al, 2012;Huang et al, 2014). IL-15 is a pleiotropic cytokine that is classified into 4α-helix bundle cytokine family (Tagaya et al, 1996).…”
Section: Introductionmentioning
confidence: 99%